Efficiency of food utilization by Dichroplus maculipennis (Orthoptera: Acrididae: Melanoplinae) on four crop plants under controlled conditions. (2nd September 2019) - Mariottini, Y.; Lange, C. E.; Cepeda, R.; De Wysiecki, M. L.
ABSTRACT: The aim of this study was to analyze the food utilization efficiencies and the relative growth and consumption rates of different developmental stages and sexes of D. maculipennis under controlled conditions on wheat, oat, corn, and soybean plants, important crops in the Pampas region of Argentina. As expected from a polyphagous species, D. maculipennis was observed to consume all four of the plant species offered. Nevertheless, the consumption of both nymphs and adults was differentiated. Oat and wheat were more consumed than corn and soybean. Females presented higher consumption rates (384.6 ± 30.64 mg/individual/day) than males (278.71 ± 24.26 mg/individual/day). Adult females had the highest growth rate, followed by nymphs of the same sex, and then adult males. The highest values of ECI and ECD were obtained in soybean; females had higher values of food efficiencies than males, and nymphs had greater values than adults. In relation to this, soybean was the highest quality food; the amount of nitrogen present in soybean was approximately twice that found in the other species. The nutritional needs of D. maculipennis might have been satisfied by feeding on low quantities of soybean, which is, among the food offered, the most "nutritionally balanced food".